2021
DOI: 10.1002/ppul.25660
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the early treatment of cystic fibrosis: Bridging the gap to highly effective modulator therapy

Abstract: Highly effective modulator therapy (HEMT) for cystic fibrosis (CF) has been touted as one of the greatest advances to date in CF care. As these therapies are now available for many older children and adults with CF, marked improvement of their nutritional status, pulmonary and gastrointestinal symptoms has been observed. However, most infants and younger children are not current candidates for HEMT due to age and/or cystic fibrosis transmembrane conductance regulator (CFTR) mutation. For these young children, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 153 publications
0
1
0
Order By: Relevance
“…This proportion is lower than in previous studies, which have shown that between 50 and 70 % of young children with CF have abnormal LCI values [31]. One influencing factor might be the advances in supportive therapies in the past years [32]. Our MBW data were also analyzed using the most recently updated software version for the Eco Medics device, which includes a correction for a previously unknown sensor error resulting in over-estimated LCI values [33].…”
Section: Comparison With Literaturementioning
confidence: 98%
“…This proportion is lower than in previous studies, which have shown that between 50 and 70 % of young children with CF have abnormal LCI values [31]. One influencing factor might be the advances in supportive therapies in the past years [32]. Our MBW data were also analyzed using the most recently updated software version for the Eco Medics device, which includes a correction for a previously unknown sensor error resulting in over-estimated LCI values [33].…”
Section: Comparison With Literaturementioning
confidence: 98%